PENGARUH JENIS UMPAN TERHADAP HASIL TANGKAPAN CUMI Loligo sp. DI PERAIRAN TUING KABUPATEN BANGKA - Fandi Ahmed Reza; Umroh Umroh; Eva Utami (Jurusan Akuakultur, Universitas Bangka Belitung, 2019)
Tuing waters become the main catchment area of ​​squid in Bangka Regency. Bait is one important factor in squid fishing trying to captivate the target with something as its prey is in the form of smell, taste, movement, shape and color both artificial baits and natural baits. The objective of the study was to analyze the catch of squid with different baits. The research was conducted in May 2016 in Tuing Waters of Bangka Regency. The method used in this research is the trial of catching the squid. Analysis of data used using Mann Whitney test. Taking data 4 times a month using squid fishing line. The results obtained between fishing with artificial feed and natural baits differ significantly because of Z count (2.17)> Z table (1.96), then H0 is rejected. This is because the waters of Tuing in May 2016 are not the season for the cultivation of the umi-squid. The catching season of squid occurs in November-Desenber in Tuing Waters. Squid is highly associated with environmental factors such as salinity, temperature and depth of water. Chemical Physical Factors The aquatic waters against the catch of squid.